The Weather-Proximity-Cognition (WPC) framework: A camping, weather, and climate change case. (December 2019) - Craig, Christopher A.
Abstract: Many businesses do not understand how changing short- and long-term weather and climatic conditions impact economic outcomes. To address this understanding gap, the Weather-Proximity-Cognition (WPC) framework is introduced. The WPC explores how spatial, temporal, and social proximity to weather and climate events or issues, as well as scale of events or issues, influences understanding and agency related to business outcomes. The WPC can be used by businesses to understand and localize weather or climate change risks and also to increase agency to engage in adaptive or mitigating efforts. Camping businesses are particularly susceptible to weather and climatic conditions. An empirical case study of two camping businesses located in popular United States destinations is presented to demonstrate the WPC framework's utility. Empirical models explained up to 61.3% of the variability in daily camping occupancy depending on geographic location, meteorological season, and camping occupancy type. WPC and case study implications are discussed. Highlights: Changing weather and climatic conditions threaten businesses, particularly nature-based businesses such as camping. The novel Weather-Proximity-Cognition (WPC) framework is introduced to enhance business understanding and agency. The WPC explores how time, space, social proximity and scale influence business understanding of weather and climate change. A case study of two camping businesses provides replicable empirical steps that can be used to analyze climatic conditions. Weather and weather events explain up to 61.3% of the variability in daily camping occupancy, an economic business outcome.